Leveraging synergistic intervals to enhance timing under multiple interval schedules - Southern, Robert (My University, 2025)
Accurate and precise timing is a fundamental aspect of many behaviors, skills, and occupations. This study tested whether structuring multiple intervals with simple multiplicative relationships enables participants to use rewards from shorter intervals as cues to improve timing on longer intervals. Across two online experiments (N = 88), participants tracked five independent fixed-interval schedules simultaneously. In Experiment 1, synergistic intervals were integer multiples of 5 s (5, 10, 20, 30, 40). In Experiment 2, nonsynergistic intervals (5, 13, 17, 21, 38) preserved the overall reinforcement rate but lacked simple multiplicative relationships. Across both experiments, two dominant strategies emerged: Steady Responders, who responded at a near-constant rate across intervals while largely disregarding programmed durations, and Interval Trackers, who showed graded sensitivity to interval length consistent with timing each interval. Synergistic interval structures did not reliably improve accuracy or precision, and scalar-like timing patterns were observed across both conditions and strategies. These findings suggest that in complex multi-interval environments, people often favor low-effort response strategies over exploiting embedded temporal cues, indicating that any benefits of synergistic intervals, if present, are subtle and difficult to detect.
Keywords: Fixed interval; Synergistic intervals; Multiple interval timing; Reinforcement; Scalar timing